Dunking for droplets: Long‐jawed spider (Araneae, Tetragnathidae) bungees on silk line to collect water droplet from pond using its mouthparts. (25th January 2022) - Gould, John; García, Luis Fernando; Valdez, Jose. W.
Abstract: Many animals have been documented to collect and subsequently transport water for several purposes besides self‐hydration. However, there are few examples where this process involves the use of external body surfaces. Herein, we report on a long‐jawed spider from the Tetragnatha genus using its enlarged jaws (chelicerae) to collect water. Field observations revealed a long‐jawed spider descending on a silk line to the surface of a body of water and collecting a large droplet of water between its jaws, which was subsequently transported to a prey item wrapped in silk within its web. As spiders feed via extra‐oral digestion, we hypothesize that this water droplet was collected to replenish water lost during a previous feeding event or to rehydrate current prey to aid in nutrient extraction and consumption. While the enlarged jaws of spiders in this genus serve in feeding and mating, our observation suggests they can also be exploited for carrying liquids. This appears to be the first documented case of water foraging and subsequent external transport among spiders, revealing a novel behaviour in this group. Abstract : While many animals have been documented to collect and subsequently transport water for several purposes, there are few examples where this process involves the use of external body surfaces. In this paper, we report on a long‐jawed spider from the Tetragnatha genus using its enlarged jaws (chelicerae) to collect a droplet of water from the surface of a waterbody beneath its web. As spiders feed via extra‐oral digestion, we hypothesize that this water was collected to replenish water lost during a previous feeding event or to rehydrate current prey to aid in nutrient consumption.